Analysis of Maktabah Syamilah as Maktabah Hadith - Siti Mirah Nuraeni; Muhammad al-Mighwar; Engkos Kosasih (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study evaluates the role and contribution of Maktabah Syamilah as a digital library in hadith studies. Maktabah Syamilah, introduced in 2005 by Dr. Hossam Salem, offers extensive digital access to hadith texts from classical to modern scholars, facilitating hadith research and learning with high efficiency. Using a qualitative approach and descriptive-analytical method, this research examines how Maktabah Syamilah supports access, search, and analysis of hadith texts compared to traditional methods. The results show that Maktabah Syamilah greatly helps researchers in finding and analyzing hadith, supporting scientific research, and preserving hadith literature in digital format. This library also improves the quality of literacy among students and facilitates lecturers in the learning process. In addition to its advantages in efficiency and ease of access, Maktabah Syamilah also has some challenges, such as dependence on technology and internet access. However, overall, the benefits offered by Maktabah Syamilah in supporting hadith studies are significant, ensuring valuable hadith literature remains available and protected from physical damage or loss.